Revenue Recognition in Software Industry : Apple Inc. Case Study - Farkašová, Anna (2017)
Rapid digitization of enterprise processes and software applications simplifying daily-life routines enhance the need for software arrangements. Based on this growing trend, the underlying thesis discusses revenue recognition for software arrangements under US GAAP, the lingua franca of financial reporting framework in software industry. The thesis examines the first industry-specific guidance - SOP 97-2, its successor ASC 605 and aims at capturing the main implications resulting from the new converged US GAAP/ IFRS revenue recognition standard ASC 606/ IFRS 15 on a case study. The five-step revenue recognition model introduced by ASC 606 is applied to the US-based technology and software seller Apple Inc. and its wide range of product portfolio including software.